Semi-specific immuno-absorption and monoclonal antibody therapy in ANCA positive vasculitis: experience in four cases. - Elliott, J; Lockwood, C; Hale, G; Waldmann, H (1998)
The treatment of renal limited systemic vasculitis usually involves a combination of cytotoxic drugs and steroids. As shown by randomised prospective controlled trial, plasmapheresis may be of additional benefit for the management of patients with renal involvement severe enough to require dialysis support. Recently, growing evidence has suggested that autoantibodies to neutrophil cytoplasm (ANCA) may play a role in the pathogenesis of the primary vasculitides by promoting neutrophil mediated endothelial cell cytotoxicity. This has led to new strategies for treatment based on firstly, the use of semi-specific immunoabsorption (IA) devices to remove circulating autoantibodies, and secondly, the use of 'Humanised' monoclonal antibodies (MAbs) with specificity for lymphocytes, particularly T lymphocytes. We have treated four patients, two with ANCA specificity for proteinase 3 (PR3), and two with specificity for myeloperoxidase (MPO). Semi-specific IA was carried out by plasmapheresis through extracorporeal online devices, using L tryptophan as the immobilised immunoabsorbant. Of the four patients who received IA, three showed substantial depletion in ANCA titres and resolution of clinical symptoms. The MAbs were subsequently used to attempt to obtain long-term control of ANCA synthesis. These results suggest that an optimal strategy for treatment of systemic vasculitis might consist of specific IA, using immobilised ANCA antigens to deplete circulating vasculotoxic antibodies, combined with MAb therapy to restore immune homeostasis.